2018
DOI: 10.7441/joc.2018.01.09
|View full text |Cite
|
Sign up to set email alerts
|

Different Approaches to the Ebit Construction and Their Impact on Corporate Financial Performance Based on the Return on Assets: Some Evidence From Czech Top100 Companies

Abstract: The paper discusses ways of measuring the financial performance of businesses. The aim is to determine to what extent the form of profit calculation influences value of return on assets (hereinafter referred to as 'ROA'), which is frequently used as an indicator for measuring financial performance. The theoretical part is focused on the comparative analysis of accounting data based on Czech practices and IFRS with the in-depth focus on interest charges and reporting requirements. There is discussed the topic o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 9 publications
0
14
0
Order By: Relevance
“…However, it is found that the weight coefficient of this indicator is 0.174. The ROA is the ratio between the aggregate of offsets and the average dose of estates obtained by an enterprise in a period of time, which presents the corporate profitability of the enterprise [22]. The weight coefficient of this index is 0.296.…”
Section: Plos Onementioning
confidence: 99%
“…However, it is found that the weight coefficient of this indicator is 0.174. The ROA is the ratio between the aggregate of offsets and the average dose of estates obtained by an enterprise in a period of time, which presents the corporate profitability of the enterprise [22]. The weight coefficient of this index is 0.296.…”
Section: Plos Onementioning
confidence: 99%
“…The dependent variable in models is operationalized by return on assets (ROA) indicator, which measures the firm's management ability to generate profits from the firm's assets (e.g. Brealey et al, 2017), and belongs to the most commonly used measure of firm performance (Strouhal et al, 2018;Rehman, 2017;Hult et al, 2008;Richard et al, 2009). All variables used in the analysis as determinants of profitability were selected based on the availability of data and based on the previous literature (e.g.…”
Section: Definition Of Variablesmentioning
confidence: 99%
“…Notably, the indices with the maximum available data are selected. These measures are stock prices [39], earnings before interest and taxes (EBIT) [40], the ratio of total liabilities to the total value of the company's assets [41], working capital on total assets [42], and earning per share (EPS) [43]. In order to integrate the metrics and create a function for each firm, the highest and the lowest numbers at a specific time are identified, and the numbers for each time are normalized.…”
Section: Calculating Financial Performancementioning
confidence: 99%